Application prototype for estimating food scraps and intake of "mugitelas" patients during the Covid-19 pandemic at Haji General Hospital Surabaya - Ridna Tri Widyaningrum (Berita Kedokteran Masyarakat, 2021)
Methods for evaluating food waste or patient intake such as weighing, FFQ, and 1-24 hours recall have many disadvantages such as the length of time used, inaccurate data entry, and poor patient memory and difficulty in estimating portion sizes so this method is often abandoned. Especially during a pandemic, which requires health workers, including nutritionists to continue to provide services by observing health protocols and the risk of transmission.Purpose: Developing an information system in the form of a web and android-based application prototype to monitor and evaluate leftover food or intake of patients at RSU Haji Surabaya, especially during the pandemic.Method: Development of information systems using the prototype method, namely 1. Problem analysis and needs analysis, 2. Appearance and interaction of applications 3. Design and architecture of prototypes and application components, 4. Implementation and application testing.Results: There is an information system in the form of an android application prototype with the name Mugitelas to monitor and evaluate the patient's food waste / intake.Conclusion: The prototype Mugitelas can be used to evaluate the patient's food waste as well as to assess the patient's. The existence of further research on the efficiency and effectiveness of Mugitelas as well as the level of acceptance of the user or nutritionist in the inpatient room for the use of this application.